2017
DOI: 10.4103/0971-4065.177142
|View full text |Cite
|
Sign up to set email alerts
|

Warfarin related acute kidney injury: A case report

Abstract: Warfarin is an oral anticoagulant used extensively in clinical practice; However, its side-effect of causing renal damage has been recently detected. The mechanism leading to renal damage is glomerular hemorrhage and red blood cell tubular casts prothrombin time. Recently, it was found that warfarin causes renal damage in patients with chronic kidney disease and is also associated with progression of renal disease. Warfarin causing acute kidney injury in patients with normal renal function is a rare manifestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 10 publications
2
18
0
Order By: Relevance
“…Various factors that can affect warfarin metabolism and induce an increase in INR are diet, drug interaction, CYP 2C9 polymorphisms etc. . In our case, there was no increase in INR value at the time of acute kidney injury, but histopathology was favourable of WRN, analogous to previous reports which may be due to the correction of coagulopathy because of stoppage of warfarin at the time admission in the emergency medical service (EMS).…”
Section: Pt Inr Serum Urea and Creatinine Values After Starting Of supporting
confidence: 87%
“…Various factors that can affect warfarin metabolism and induce an increase in INR are diet, drug interaction, CYP 2C9 polymorphisms etc. . In our case, there was no increase in INR value at the time of acute kidney injury, but histopathology was favourable of WRN, analogous to previous reports which may be due to the correction of coagulopathy because of stoppage of warfarin at the time admission in the emergency medical service (EMS).…”
Section: Pt Inr Serum Urea and Creatinine Values After Starting Of supporting
confidence: 87%
“…Accordingly, the term "anticoagulant-related nephropathy" (ARN) is preferred. Since the seminal report of pathologic features of warfarin-related nephropathy, 1 several investigators published case reports and retrospective studies showing AKI in association with different anticoagulants, including multiple case reports and case series that describe warfarin-related nephropathy, [7][8][9][10][11][12] case reports of dabigatran-associated AKI, [13][14][15][16][17] a case report of AKI in a patient with thrombocytopenia, 18 and a case of biopsy-proven ARN in a patient receiving antiplatelet medications. 19 Given the existing data for this newly described entity and the presence of multiple causes for anticoagulation, we explored our database of existing kidney biopsies since our initial description of ARN to describe ARN with additional details, including agents that may predispose to this unusual cause of AKI.…”
mentioning
confidence: 99%
“…The current work clearly illustrated that the administration of 3 mg/kg body weight of KT together with 0.3 mg/kg body weight of WR for six consecutive days induced vascular congestion together with variable degrees of degeneration and vacuolation in the glomeruli and tubular cells of all treated groups, being more vigorously attacking the cortical tissues in KT/WR treated rats. The major mechanisms for WR-induced renal toxicity were previously reported as glomerular hemorrhage and tubular dysfunction by obstruction due to RBC casts (Mendonca, Gupta, Valsan, & Tewari, 2017;Ozcan et al, 2012). Similar to Chana et al (2014) who revealed that KT induced acute kidney injury, another NSAID, diclofenac sodium, was found to induce the congestion in the blood vessels, the degeneration in nephrons, and the increase in the connective tissue in rat kidneys (Khoshvakhti et al, 2015).…”
Section: Discussionmentioning
confidence: 67%
“…The serum levels of urea and creatinine are screening tests of renal function; their values remain within the normal range until more than 50% of renal function is lost (Mendonca et al, 2017). At all stages of renal insufficiency, the creatinine is a much more reliable indicator of renal function than the urea because the urea is far more likely to be affected by dietary and physiologic conditions not related to renal function.…”
Section: Discussionmentioning
confidence: 99%